PECULIARITIES OF THE UKRAINE’S FINANCIAL MARKET AND ITS IMPACT ON THE BUSINESS ENVIRONMENT - Yereshko, Julia; Pourahmadi, Shayan; Skyba, Hanna; Kubai, Oksana (Revista Gestão & Tecnologia, 2023)
Solving the problems of economic stabilization and ensuring the sustainable development is directly related to the formation of active innovative activities, the development and implementation of innovative strategies both at the macroeconomic scope and at the level of individual economic entities. The study of financial and capital markets as an indicator of economic growth and investment activity revealed disproportions. portfolio investment, as well as the fall of the stock market of Ukraine compared with the capitalization of domestic stock exchanges with developed economies. To solve this problem, large incentives are needed, including appropriate tax incentives for banks and enterprises, the development of competitive innovative projects on the basis of which capital in the real sector will provide profitability compared to foreign exchange assets or capital placement abroad in conditions of long-term stability.